Freight Rates on Coal : hearings before the United States House Committee on Interstate and Foreign Commerce, Sixty-Third Congress, first session, on Aug. 22, 1913. (U.S. Congressional Hearings., 1913)
Considers resolution to authorize Federal investigation of prices, production costs, and freight rates in the Pennsylvania anthracite mining industry.